ATG4: More Than a Protease?. Issue 7 (July 2021) - Ketteler, Robin; Tooze, Sharon A.
Abstract : The ATG4 proteases are key regulators of autophagy. Until recently it was thought that their main function was to mediate the processing of ATG8 family members. A new study by Nguyen et al . reveals a role for ATG4s, independent of their catalytic activity, and proposes novel functions in mediating lipid transfer and mitophagy.